RESIN MOLDING APPARATUS AND METHOD FOR MANUFACTURING RESIN MOLDED ARTICLE - MIZUMA KEITA (2019)
The present invention provides a resin molding apparatus capable of suppressing warpage in a resin molded article. A resin molding apparatus (10) performing resin molding by sealing a molding target with thermosetting resin comprises: a molding form (111) including a first form, a lower form (1111), with a cavity and a second form, an upper form (1112), with a molding target mounting portion on which the molding target is mounted; a molding form heating device, a molding form heater (112), heating the molding form (111) at the temperature within the temperature range in which the thermosetting resin is hardened; a temperature retaining chamber (13) fabricated with the molding form (111), storing the molding target and an intermediate molded article (M), which is made of the thermosetting resin not completely hardened, and maintained at the temperature within the temperature range; and an intermediate molded article transferring device, a first transferring device (12), transferring the intermediate molded article (M) from the molding form (111) to the temperature retaining chamber (13) while the intermediate molded article (M) is kept at the temperature higher than a room temperature and lower than an upper limit of the temperature range. 본 발명의 과제는 수지 성형품에 휨이 발생하는 것을 억제할 수 있는 수지 성형 장치를 제공하는 것이다. 수지 성형 장치(10)는, 성형 대상물을 열경화성 수지로 밀봉함으로써 수지 성형을 행하는 장치이며, 캐비티가 마련된 제1 형[하형(1111)]과, 성형 대상물을 장착하는 성형 대상물 장착부를 구비하는 제2 형[상형(1112)]으로 이루어지는 성형 형(111)과, 성형 형(111)을, 상기 열경화성 수지가 경화되는 온도 범위 내의 온도로 가열하는 성형 형 가열 기구[성형 형 히터(112)]와, 성형 형(111)으로 제작되는, 성형 대상물 및 완전히는 경화되지 않은 상기 열경화성 수지로 이루어지는 중간 성형품(M)을 수용하고, 상기 온도 범위 내의 온도로 유지하는 온도 유지실(13)과, 중간 성형품(M)을, 실온보다도 높고 또한 상기 온도 범위의 상한 이하의 온도로 유지하면서 성형 형(111)으로부터 온도 유지실(13)로 반송하는 중간 성형품 반송 기구[제1 반송 기구(12)]를 구비한다.